Value of Persistent Infection for Airway Remodeling of Bronchial Asthma in Children. Approaches to Treatment and Prevention - O.Ye. Chernyshova (Zaslavsky O.Yu., 2015)
This article provides information on the impact of persistent intracellular infection on airway remodeling in asthma in children. There were described the effect of matrix metalloproteinase, tissue inhibitor of matrix metalloproteinase, transforming growth factor antibodies to collagen type III, endothelin-1 on the process of morphological airway remodeling such as hypertrophy of smooth muscles, the enhanced neovascularization, epithelial cell hyperplasia, collagen deposition and compression of the basal membrane observed in bronchial asthma in children. There were determined the etiopathogenetic methods of treatment, in particular putting on acyclic nucleosides or macrolide depending on diagnosed infections, immunomodulators and α2β-interferon to reduce airway remodeling processes and the severity of the disease and to decrease disability.